The Montessori child : a parent's guide to raising capable children with creative minds and compassionate hearts - Davies, Simone; Uzodike, Junnifa (Workman Publishing, 2024)
"From the bestselling authors of The Montessori Toddler and The Montessori Baby, The Montessori Child guides parents in using the principals of Montessori to raise their school-aged children in ways that assist their development and foster a respectful relationship between parent and child and world. When children are given independence, the tools to succeed, and the encouragement to build on their abilities, it's amazing what they can achieve. The newest book in the bestselling Montessori series is an everything-you-need-to-know guide to raising your school-aged child (from 3-12 years old, with a bonus chapter for the teen years) in the Montessori way. Educators Simone Davies and Junnifa Uzodike provide an in-depth, practical guide to incorporating Montessori principles into readers' everyday lives, with advice on everything from setting up your home in ways that encourage curiosity and independence to supporting your child's social and moral development with a balance of limit-setting and age-appropriate freedoms. The book includes dozens of hands-on activities to help foster your child's love of numbers and literacy, art and science, and ones that encourage community-building, social awareness, and connection with the natural world. The Montessori Child offers a powerful alternative for parents who feel that family life has gotten too complicated by showing parents how to make more intentional choices for your family, how to better understand the needs of your children, and support them as they develop their unique potential"--